Pengamanan Short Message Service ( SMS ) Menggunakan Algoritma Vibranium Cipher - Nifeyani Gulo (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2021)
Security of SMS (Short Message Service) is one of the activities carried out so that SMS from an undisclosed information cannot be known by other people except those who are given the right to do so. There are several approaches to SMS security techniques that are still used by a number of people today, including by applying cryptographic techniques, steganographic techniques, watermarks and other techniques. A message that is not encoded or encrypted is called plaintext, while a message that has been encoded with a cryptographic algorithm is called ciphertext. . Cryptography is a technique of securing messages by encrypting the contents of the message so that it is safe, while the short message service is a service provided by cellular or Android phones to send and receive messages. The tapping occurs on the communication line, so the SMS text will be very easy to read by tapping, in data encryption, especially the one discussed, namely SMS, there are various algorithms that can be used to secure data, one of which is the vibranium cipher algorithm which uses blocks with a size of 128 bits which can help users to send short messages safely, quickly and easily